2014
DOI: 10.3109/0886022x.2014.934693
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury in the elderly hospitalized patients

Abstract: The AKI represents a frequent complication in the elderly patients with longer hospital stay and increased mortality and morbidity. Our results show that dialytic support requirement is an independent predictor of permeant kidney injury in the elderly AKI patients. Older age, low diastolic blood pressure, high CRP and low hemoglobin levels were independent risk factors for mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 19 publications
1
18
1
Order By: Relevance
“…In our cohort, the rate of all-cause mortality was 26.8, 34.1, 37.1, and 39.3% at 1, 2, 3 and 4 years, respectively. A few studies investigating predictors of mortality following hip fracture have identified age, dementia, malnutrition, and comorbidities [4,7,10,13,20]. Our study suggests that AKI during hospitalization is an important predictor of long-term mortality.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…In our cohort, the rate of all-cause mortality was 26.8, 34.1, 37.1, and 39.3% at 1, 2, 3 and 4 years, respectively. A few studies investigating predictors of mortality following hip fracture have identified age, dementia, malnutrition, and comorbidities [4,7,10,13,20]. Our study suggests that AKI during hospitalization is an important predictor of long-term mortality.…”
Section: Discussionmentioning
confidence: 52%
“…Early diagnosis of AKI would be possible, and elderly patients with severe AKI did not undergo surgery. The reported incidence of AKI in elderly patients undergoing hip fracture surgery ranges from 15.3–24.4% according to the definition of AKI and varies with the considered population [2,3,6,8,10,30]. Elderly patients are particularly susceptible to developing AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality in the elderly with AKI varies in the literature from 23% [17] to 54% [13] according to the mean age of the patients, severity of illness and criteria used to define AKI. In our series, almost 70% of the nonagenarians with AKI died.…”
Section: Discussionmentioning
confidence: 99%
“…Tang et al demonstrated that elevated serum CRP concentrations were associated with increased serum creatinine and urea concentrations ( P < 0.01) in patients with AKI; CRP concentrations subsequently fell after recovery from AKI . In older patients with AKI, CRP was an independent risk factor for mortality . CRP has also been studied for its ability to predict risk for AKI.…”
Section: Discussionmentioning
confidence: 99%